The Most Space-Effective. A new squash pavilion: let’s play like everybody is watching! - Fixman, Yossi (project baikal, 2017)
TPoint and ASB have created a pure and simple transparent functionality concept that is turning squash from a limited indoor game to a dynamic outdoor success. This concept is embodied in the world’s first smart outdoor squash courts.